The Effectiveness of Science-Based Learning towards Students’ Understanding of Complex Analysis Courses - Mariamah Mariamah (IJECA (International Journal of Education and Curriculum Application), 2018)
The purpose of this study is to describe the effectiveness of science-based learning drill towards students' understanding of complex analysis courses. This research employed experimental procedure with one group posttest design. The experimental group consisted of 20 sixth semester students taking complex analysis courses. They were treated with drills on science-based learning procedure followed with a post test that is composed of seven questions. To measure the effectiveness of the procedure, t-test was applied. With a standard value of 70 (value = 70), the computation using SPSS 16 program showed the t test results at a significant level of 5% was 1. 78, t table 1.327, and degrees of freedom (dk = 20-1). Because t arithmetic is greater than t table, the alternative hypothesis (Ha) is accepted. It can be concluded from the statistical analysis that science-based learning drills are effective to influence students’ understanding of materials in complex analysis courses.The purpose of this study is to describe the effectiveness of science-based learning drill towards students' understanding of complex analysis courses. This research employed experimental procedure with one group posttest design. The experimental group consisted of 20 sixth semester students taking complex analysis courses. They were treated with drills on science-based learning procedure followed with a post test that is composed of seven questions. To measure the effectiveness of the procedure, t-test was applied. With a standard value of 70 (value = 70), the computation using SPSS 16 program showed the t test results at a significant level of 5% was 1. 78, t table 1.327, and degrees of freedom (dk = 20-1). Because t arithmetic is greater than t table, the alternative hypothesis (Ha) is accepted. It can be concluded from the statistical analysis that science-based learning drills are effective to influence students’ understanding of materials in complex analysis courses.